Analysis of the Usability of the Badkidstore Indonesia Website Using the System Usability Scale (SUS) Method - Achmadhin Tristan Syafaat; Sucipto; Muhammad Najibulloh Muzaki (Proceeding International Conference on Digital Education and Social Science, 2025)
The development of e-commerce in Indonesia requires business actors to provide websites that not only function as a marketing medium, but are also able to provide a good user experience. The Badkidstore Indonesia website is an e-commerce platform that sells casual wear fashion products for young soccer players. As the main means of transactions, this website must have good usability so that users can shop comfortably and efficiently, although there are still obstacles in navigation, access speed, and purchase flow. This study aims to assess the usability of the Badkidstore Indonesia Website based on user perception using the System Usability Scale (SUS) method. The research was carried out in a descriptive quantitative manner through a SUS questionnaire containing 10 Likert scale statements which were distributed to 100 active users, then analyzed using the calculation of SUS scores. The results of the study showed that the Badkidstore Indonesia website obtained an average SUS score of 69.9 which was in Grade C- with the category "OK" and the Acceptable level. Based on the Net Promoter Score (NPS) classification, the score belongs to the Passive category, which shows that users are quite satisfied but not yet encouraged to recommend the website to other users. Based on the results of the research, the Badkidstore Indonesia website has met the minimum usability standards, but it still needs further development. Improvements are suggested on access speed, interface consistency, and purchase flow. This research is limited to the use of the SUS method, so further research is recommended to combine other methods such as UEQ or WebQual and retest after system improvement.